Application of the toolbox-matlab in the estimation of total efficient management ot energy in Moa, Holguín, Cuba - Montero-Laurencio, Reineris; Góngora-Leyva, Ever (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2017)
Using the parametric modeling it is demonstrated the possibilities of the employment of identificaction Matlab Toolbox to predic consumptions and energy indicators. A summary of the Holguín's province hotels energetic situation is presented, regarding the energetic carriers' consumption structure and the opetarional characteristics which decide their behavior. A representative hotel is chosen, as case of study in which the tools of the energetic management are applied.